Canopy Achitecture, Biomass and Fruit Production of Solanum nigrum L. as Determined by Nitrogen Application - Santosa, Edi; Putriantari, Marcella; Nakano, Hajime; Mine, Yoko; Sugiyama, Nobuo (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2017)
ABSTRACT Demand on fruits of Leunca (Solanum nigrum L.) is increasing in Indonesia due to a rapid expansion of ethnic restaurants, especially Sundanese restaurants. Most fruits come from semi-intensive cultivation in intercropping system, leading to low productivity. In order to improve productivity, nitrogen experiment was carried out at field of Leuwikopo Farm of Bogor Agricultural University, Bogor-Indonesia, during rainy season from December 2013 to April 2014. Four levels of nitrogen, i.e., 0, 60, 120, and 180 kg N ha-1, were arranged in a randomized complete block design with four replicates. The results revealed that canopy architecture, dry matter and fruit production, and fruit quality were highly affected by nitrogen application. Increasing nitrogen levels increased biomass and fruit production. Plants treated with nitrogen at level of 60 kg ha-1 produced ideal height for local labor and stable weekly fruit production than other levels. Hence, N fertilizer is essential for achieving high productivity of S. nigrum.Keywords: canopy shape, fruit load, indigenous vegetable, leunca, ranti kebo ABSTRAK Permintaan buah Leunca (Solanum nigrum L.) terus meningkat di Indonesia sejalan dengan perkembangan restoran etnis khususnya restoran Sunda. Sebagian besar buah leunca berasal dari tanaman sampingan secara tumpangsari, sehingga produktivitas rendah. Dalam rangka meningkatkan produktivitas, percobaan pemberian nitrogen dilakukan di Kebun Percobaan Leuwikopo IPB, Bogor pada musim hujan Desember 2013 sampai April 2014. Nitrogen diberikan empat taraf yaitu 0, 60, 120, dan 180 kg N ha-1, yang disusun dalam rancangan acak kelompok dengan empat ulangan. Hasil menunjukkan bahwa bentuk kanopi, produksi bahan kering dan produksi buah serta kualitas buah dipengaruhi oleh pemberian nitrogen. Peningkatan dosis nitrogen meningkatkan bahan kering dan produksi buah. Tanaman dengan perlakuan 60 kg N ha-1 menghasilkan tinggi yang ideal bagi pemanen, dan hasil mingguan yang stabil dibandingkan dengan taraf yang lebih besar. Oleh karena itu, pemupukan nitrogen penting dilakukan untuk meningkatkan produktivitas leunca.Kata kunci: beban buah, bentuk kanopi, leunca, ranti kebo, sayuran tradisional